(untitled) (American Journal of Islam and Society, 2010)
Three decades after its 1979 Islamic Revolution, Iran’s foreign policy remains committed to “exporting the revolution” (sodoure enqelab). Through this policy, the Islamic Republic of Iran wants to make the world safe for not only Islam and Muslims, but for all oppressed people around the world. The idea is based on the ideology of Imam Khomeini, who presented it in a general way in his important work on jurisprudence. To him, the role of Imam is to preserve the Islamic ummah’s unity, liberate the Islamic homeland from the seizure and influence of the colonizers and their puppet governments, and initiate the just Islamic government. In this article, I explore the politics, ends, and means of exporting the revolution in the overall context of Iran’s foreign policy as well as show how the divinely inspired nature of the revolution was to bring Islamic justice to humanity and the various peaceful and coercive means it adopted to provide happiness, well-being, and salvation to all nations. To Imam Khomeini and his followers, the final end of “great Islamic community” could not be achieved in the current arrogant international society without helping the disintegrated Muslim nations to unite with each other and using adequate force.